Public Knowledge, Attitude, and Perception of Human Papilloma Virus in Northern Border Province, Saudi Arabia: A Cross-Sectional Study - Ahmed S. Alshrari (Journal of Pure and Applied Microbiology)
This cross-sectional study intended to measure human papillomavirus (HPV) and HPV vaccine awareness among the society residing in the Northern Border Province of Saudi Arabia and its adjacent regions. A 26-item questionnaire was used to attain the objectives of this study. Cronbach’s alpha of 0.878 was used to assess the tool’s reliability. SPSS version 20® was used for statistical analysis. Both descriptive and inferential statistics were employed and p-value < 0.05 was deemed statistically significant. Overall, 1041 people participated in this study. Most respondents were 18-45 years old. HPV awareness is found to be higher in women than men. Education was not the primary factor affecting HPV knowledge among respondents. Most respondents were conscious that HPV can instigate cervical cancer; however, women were more knowledgeable than men. Most men and women were unaware of HPV vaccine availability in their region, and most advocated for pre-marital immunization. This survey found that most northern border respondents knew little about HPV, its prevention, and its vaccine schedule. Public health education is needed to address respondent knowledge gaps in these regions and increase vaccination success by sharing evidence-based information about HPV vaccine safety, clinical efficacy, and complications.